The influence of Self-Concept into the Self Esteem in the Orphanage - Erna Multahada; Michelle Mabelle (TARBIYA: Journal of Education in Muslim Society, 2015)
Abstract The influence of self-concept into the selfesteem in the orphanage adolescent Akhiruz Zaman is the aim of this research. The participant is from 80 adolescents (in age 13-21) who stay in orphanage X. the subject is taken randomly using two questionnaire, they are: self-concept questionnaire and selfesteem questionnaire. The result is there is the influence of self-concept into the self-esteem of adolescent. The contribution of it is 18.5% with significant P = 0,000 which is very significant. It has the rest in 81, 5% caused by other factors. It concludes that the matter of adolescent selfesteem that stays in orphanage, one of the factors is caused by the concepts of themselves.. Abstrak Pengaruh konsep diri kterhadap kepercayaan diri di panti asuhan remaja Akhiruz Zaman adalah tujuan dari penelitian ini. Peserta meliputi 80 remaja (usia 13-21 tahun) yang tinggal di panti asuhan X. Subjek penelitian dipilih secara acak menggunakan dua kuisioner, yaitu kuisioner konsep diri dan kuisioner kepercayaan diri. Hasil menunjukkan bahwa terdapat pengaruh konsep diri dengan kepercayaan diri pada remaja. Kontribusi sebesar 18,5% dengan signifikansi p = 0,000 yakni sangat signifikan 81,5% sisanya, disebabkan oleh faktor-faktor lain. Dapat disimpulkan bahwa masalah kepercayaan diri remaja yang tinggal di panti asuhan, salah satunya disebabkan oleh konsep diri mereka. How to Cite : Multahada, E. Mabelle, M. (2015). The Influence of Self-Concept into the Self Esteem in the Orphanage Adolescent  Akhiruz Zaman Bekasi, West Java. TARBIYA: Journal Of Education In Muslim Society, 2(2), 117-122. doi:10.15408/tjems.v2i2.2804. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v2i2.2804